(untitled) (The Batuk, 2019)
The main concern of this study is to identify the relationship between intrinsic motivation and professional ethics of Federal Affairs and Ministry of General Administration office employees. With respect to this context, the study has been conducted to answer the following questions. Does the professionalism and self-motivation have create causality relation in the public sector employees? What are the factors of intrinsic motivation regulating on the public sector employees? From literature review public sector job trustworthiness as dependent variable and autonomy, relatedness and competency independent variables were identified. Researchers used the both quantitative and qualitative approach to explore the behavior, perspectives, experiences and feelings of people and emphasize the understanding of intrinsic motivation on professional ethics in public sector. Non-probability sampling (purposive sampling) applied in this study. The findings of this study showed that Public sector job trustiness had significant relationship with intrinsic motivational psychological need factors such as: Autonomy, Relatedness and Competence.